PENGARUH VIRUS CORONA (COVID-19) TERHADAP PENERIMAAN MAHASISWA BARU DI UNIVERSITAS INDO GLOBAL MANDIRI - Afid Afendi; Intan Gustia; Nova Yanti Maleha (Jurnal Ilmiah Mahasiswa Ekonomi Syariah (JIMESHA), 2021)
The Corona virus (Covid19) is a virus that first appeared in Wuhan, China at the end of 2019, then Covid News entered Indonesia Around February in Indonesia, it began in March 2020, starting with a positive victim in the city of Depok. After that an increase in cases occurred throughout the Greater Jakarta area so that it became a red zone area. The COVID-19 pandemic is a devastating disaster for all inhabitants of the earth. All segments of human life on earth are not disturbed, without exception of education. Many countries have decided to close schools, colleges and universities, including Indonesia. From the results of the research conducted, there are many impacts on the field of education, starting from students who have to study online / dare to even new student applicants who have entered their favorite university in the following year. Universities / colleges also feel the same way. New Student Admissions (PMB) have decreased significantly. The campus is doing various ways to increase the interest of prospective applicants to enter their tertiary institutions.